Characteristics and Flow Dynamics of Bubble-in-Chain Rising in a Quiescent Fluid. (October 2021) - Li, Si-ying; Xu, Yang; Wang, Jin-jun
Highlights: Instantaneous measurements of bubble shape and the bubble-induced flow by the combination of shadowgraphy and PIV/LIF. The freely rising bubble could be divided into three stages of rectilinear rising, transition regime, and zigzagging. Increase of bubble aspect ratio and disturbance from leading bubbles are responsible for bubble path instability. The bubble-induced flow presents strong entrainment ability in the zigzagging stage. Abstract: In the present study, we experimentally investigated the freely rising of bubble-in-chain and the evolution of bubble-induced flow for a quiescent fluid. Quantitative data on bubble morphology, kinematics, and bubble-induced flow dynamics were obtained by combining the methods of shadowgraphy and laser-induced-fluorescence particle image velocimetry (PIV/LIF). Under the current experimental condition, after detached from the orifice, the rising of the bubble can be divided into three stages: rectilinear rising, transition regime and zigzagging. In the rectilinear rising stage (0 < y/Dn < 12), the bubble-induced flow is dominated by a pair of counter-rotating vortices, which rise together with the bubble moving, i.e., the standing eddies. Each bubble experiences an acceleration along the orifice centerline, and gradually becomes flattened with its aspect ratio increasing. At y/Dn ≈ 12, the bubble aspect ratio reaches the maximum ( χ ≈ 4) and the induced wake vortices are significantly strengthened. Coupled with the destabilizing effect of disturbance from previous leading bubbles, the wake flow becomes unstable leading to the onset of wake vortex shedding that triggers the bubble path instability. As a result, the bubble deviates from the rectilinear path and goes into the transition regime. As rising to y/Dn ≈ 30, the bubble is strongly affected by the wake from previous bubbles since the vorticity has not been accumulated to trigger the next vortex shedding. Thus, the bubble enters in the zigzagging stage with its trajectory exhibiting significant differences among different bubbles. In particular, the bubble-induced flow in the zigzagging stage has the strong entrainment ability, which might be helpful for applications using bubbles for enhancing the mixing and transport of liquids.